Clustering As the Mechanism of Enhancement of the Technological Competitive Ability of the Enterprise - Milko, Inna (International Journal of Economics and Financial Issues, 2014)
The article generalizes the scientific approaches to understanding the concept of “clustering”. The conceptual approaches to definition of the function and meaning of clustering as a mechanism of enhancement of technological competitive ability of the enterprise received further development. The generalization of the scientific approaches to the conceptual and categorical instrument let separate the place of the mechanism in the system of management of the technological competitive ability of the enterprise. The systematization of the modern state of the technological development of the national industrial enterprises let detect actual problems of enhancement of their competitive ability on the basis of clustering. Keywords: clustering; effectiveness; competitive ability; industrial production; technology; profit; synergetic effect; strategy JEL Classifications: F20; F23; F63